2022
DOI: 10.1177/19386400221079491
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Complications of the INFINITY Total Ankle: A Systematic Review

Abstract: Ankle arthroplasty is a viable treatment option for end-stage ankle arthritis and has shown improvements in pain relief, motion, as well as function and gait. Newer generation total ankle prostheses have improved instrumentation and surgical techniques, as well as minimal bone resection on both the tibia and talus. The purpose of this systematic review was to determine the short-term clinical success of the INFINITY total ankle, including the common complications and rate of revision with this prosthesis. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…In total, 143 patients (148 ankles) were recruited between October 2017 and June 2020 at 9 centers (range of cases per site [6][7][8][9][10][11][12][13][14][15][16][17][18]. A total of 116 completed 2-year follow-up.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 143 patients (148 ankles) were recruited between October 2017 and June 2020 at 9 centers (range of cases per site [6][7][8][9][10][11][12][13][14][15][16][17][18]. A total of 116 completed 2-year follow-up.…”
Section: Study Populationmentioning
confidence: 99%
“…It is a fixed-bearing implant that has approved options for talar interchangeability with flat-topped (INBONE, Stryker, Kalamazoo, MI) domes as needed and uses extramedullary alignment guides but also has the capacity for computed tomography (CT)–derived patient-specific cutting guides. 6,13,24…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of total ankle arthroplasty (TAA) as a surgical treatment for end-stage ankle osteoarthritis (OA) is increasing because of improved clinical outcomes from modern design features in TAA. 1,3,6,8,9,20,28 A recent survey of the National Inpatient Sample database in the United States reported that a total of 5315 TAAs were performed in 2017, a more than 5-fold increase in incidence compared with 2005. 31 The increase in utilization of TAA has been driven by factors such as an aging population, an increased prevalence of arthritis, and advancements in implant technology.…”
Section: Introductionmentioning
confidence: 99%
“…design TAA. 5,6 Thus, the purpose of this review was to provide an updated overview of ankle OA, including pathophysiologic and diagnostic considerations. We will also address developments in the nonsurgical and surgical treatment of the condition.…”
mentioning
confidence: 99%